2017
DOI: 10.1021/acs.biomac.6b01721
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembly of Recombinant Silk as a Strategy for Chemical-Free Formation of Bioactive Coatings: A Real-Time Study

Abstract: Functionalization of biomaterials with biologically active peptides can improve their performance after implantation. By genetic fusion to self-assembling proteins, the functional peptides can easily be presented on different physical formats. Herein, a chemical-free coating method based on self-assembly of the recombinant spider silk protein 4RepCT is described and used to prepare functional coatings on various biomaterial surfaces. The silk assembly was studied in real-time, revealing the occurrence of conti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
111
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 52 publications
(121 citation statements)
references
References 40 publications
10
111
0
Order By: Relevance
“…When the flow rate is kept this low, the adsorption behavior is considered to be similar to that of a still solution. Previously reported results show that 4RepCT silk coatings obtained during QCM-D measurements under the same conditions as in our studies result in randomly oriented rather than aligned nanofibrils, confirmed by AFM 33. A buffer baseline was established for at least 30 min.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…When the flow rate is kept this low, the adsorption behavior is considered to be similar to that of a still solution. Previously reported results show that 4RepCT silk coatings obtained during QCM-D measurements under the same conditions as in our studies result in randomly oriented rather than aligned nanofibrils, confirmed by AFM 33. A buffer baseline was established for at least 30 min.…”
supporting
confidence: 88%
“…QSX-301 Au sensors (Biolin Scientific) for quartz crystal microbalance with dissipation (QCM-D) were cleaned and rendered hydrophobic using 2 mM 1-undecanethiol as previously described. 33…”
Section: Solid Surfacesmentioning
confidence: 99%
“…Almost all studies reported that silk coatings increased smoothness and rendered the surfaces more hydrophilic . Although hydrophilic, it was found that 4RepCT coating formed a nanofibrillar structure . However, perhaps the most exciting result of this study was the nearly undetectable immune response as well as the slow biodegradation in vivo.…”
Section: Implant Coatingsmentioning
confidence: 63%
“…The silk coating assembled into fibrils on the surface, and these nanofibrous coatings, especially FN‐4RepCT, improved viability, spreading, and proliferation of HDMEC and human dermal fibroblasts. A decrease in S. aureus density was also observed on both 4RepCT and Mag‐4RepCT …”
Section: Implant Coatingsmentioning
confidence: 73%
“…It has previously been reported that silk proteins adsorb at a constantly increasing rate on a surface and, through protein− protein interactions, form patterns similar to the ECM within connective tissues. 11 Thereby, added cells can sense a microenvironment similar to the native and develop essential cell-ECM attachment points through cell receptors. 10 Many of these cell receptors are transmembrane proteins (e.g., integrins) that bind to ECM proteins (e.g., fibronectin and laminin) and key mediators in cell adherence, migration, and proliferation.…”
Section: Discussionmentioning
confidence: 99%